Evaluating supervised concept drift detection for online imputation on wearable data streams with changing missing mechanisms - S. Lima, Afonso M.; Q. Mota, Matheus; Cardoso, Leonardo S.; Sousa, Elaine P. M. de (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2026: Anais do XLI Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd.2026.249498, 2026)
Wearable data streams often contain missing values, for which there is uncertainty about the cause of the missingness. Further, this missingness may also change throughout the stream processing. Our study evaluates the effectiveness of concept drift detectors applied in a supervised manner for online imputation on heart rate data streams collected from wearable devices. Experiments were conducted under changing missing mechanisms scenarios, utilizing the Hoeffding Adaptive Tree regressor alongside three concept drift detectors for monitoring model error: Page-Hinkley, Kolmogorov-Smirnov Windowing, and Adaptive Windowing. We also compared it with baselines Hoeffding Tree and mean imputation. Our results show that supervised concept drift detection yields worse performance than non-aware concept drift approaches. This indicates that supervised detectors may be insufficient to address data distribution changes caused by missing values, highlighting the need for further research.